Analysis of the colour characteristics of Jiaodong paper-cutting art in "Calabash Brothers" based on the perspective of Barthes’s semiotic - Yun, Zhang; Padil, Md Nagib; Ramlie, Md Khairul Nizam; Shibo, Zhou (Universiti Teknologi MARA, Perak, 2025)
Based on Barthes’s semiotic perspective, this study deeply analyses the colour design characteristics of Jiaodong paper-cutting art in the classic animation "Calabash Brothers". The study uses qualitative research methods to explore how it conveys deep cultural connotations and emotional expressions through visual elements, aiming to reveal the semiotic significance and visual expression of traditional folk art in modern film and television works. Through the theoretical framework of Barthes's semiotics and from the two levels of "signifier" and "signified" of symbols, we analyse how the formal characteristics and cultural connotation of Jiaodong paper-cutting art are inherited and reproduced in "Calabash Brothers".The article first sorts out the unique visual language of Jiaodong paper-cut art, including its use of bright primary colours, strong colour contrast, and expression of emotional tension. Secondly, it explores how these characteristics are reflected in animation and form a distinctive national artistic style. The "Calabash Brothers" cartoon absorbs the essence of Jiaodong paper-cutting art and recreates it through the animation medium, which not only gives new vitality to traditional art, but also enhances the expressiveness and communication power of its symbols. This analysis aims to provide theoretical support for the modern application of traditional art and promote its new vitality in a broader cultural context.